Efeitos comportamentais e neuroquímicos da liraglutida e da associação com o levetiracetam em camundongos submetidos ao modelo de abrasamento induzido por pentilenotetrazol - Souza, Alana Gomes (2017)
Epilepsy is one of the most prevalent neurological diseases in the world and 30% of patients are refractory to treatment. In addition, studies show a close relationship between epilepsy and psychiatric comorbidities. Kindling has been widely used as a model for studying epilepsy and different neuropsychiatric disorders associated with it. Studies have shown that levetiracetam (LEV) reduces the severity of seizures in animals in the pentilenotetrazole (PTZ)-induced kindling model, but there is a growing concern with possible neurobehavioral adverse reactions due to its use. On the other hand, there is evidence of the promising effects of the use of GLP-1 receptor agonists, such as liraglutide (LIRA), in brain disorders. Thus, the present study aims to investigate the behavioral and neurochemical effects of liraglutide in mice treated or not with levetiracetam submitted to PTZ- induced kindling model. Male mice received PTZ on alternate days for 21 days; before to PTZ administration, the animals were treated with LIRA and / or LEV or saline. Observation of the stages of convulsion by the Racine scale and the behavioral tests Open Field, Elevated Plus Maze and Forced Swim, to evaluate of anxiety-like and depressive-like behaviors, and Passive Shock Avoidance and Novel Object Recognition, to verify cognitive performance, were carried out. Moreover, alterations in oxidative stress in the prefrontal cortex (CPF), hippocampus (HC) and striatum (CE); and in brain derived neurotrophic factor (BDNF) in HC were evaluated. The LIRA, alone, delayed the establishment of the kindling, but was not able to avoid it; prevented the anxiety-like and depressive-like behaviors caused by the PTZ- induced kindling and at the dose of 150μg / kg had a beneficial effect on spatial and aversive memory. In the neurochemical parameters, LIRA 150, associated with LEV, reduced nitrite levels in HC and CPF and MDA in all areas; increased levels of GSH also in the three areas and of BNDF in HC. The LEV, on the other hand, showed anti-kindling potential and reduced the parameters of oxidative damage, but it was not able to prevent the similar anxiety-like and depressive-like behaviors and the cognitive dysfunction, caused by the PTZ- induced kindling. Therefore, it is suggested that association with LIRA (150 μg / kg) may be considered promising for the treatment of comorbidities associated with epilepsy, since it has beneficial effects on neurobehavioural functions, without interfering with the anticonvulsant potential of LEV.